A dual‐function RNA balances carbon uptake and central metabolism in Vibrio cholerae. (6th October 2021) - Venkat, Kavyaa; Hoyos, Mona; Haycocks, James RJ; Cassidy, Liam; Engelmann, Beatrice; Rolle‐Kampczyk, Ulrike; von Bergen, Martin; Tholey, Andreas; Grainger, David C; Papenfort, Kai
Abstract: Bacterial small RNAs (sRNAs) are well known to modulate gene expression by base pairing with trans ‐encoded transcripts and are typically non‐coding. However, several sRNAs have been reported to also contain an open reading frame and thus are considered dual‐function RNAs. In this study, we discovered a dual‐function RNA from Vibrio cholerae, called VcdRP, harboring a 29 amino acid small protein (VcdP), as well as a base‐pairing sequence. Using a forward genetic screen, we identified VcdRP as a repressor of cholera toxin production and link this phenotype to the inhibition of carbon transport by the base‐pairing segment of the regulator. By contrast, we demonstrate that the VcdP small protein acts downstream of carbon transport by binding to citrate synthase (GltA), the first enzyme of the citric acid cycle. Interaction of VcdP with GltA results in increased enzyme activity and together VcdR and VcdP reroute carbon metabolism. We further show that transcription of vcdRP is repressed by CRP allowing us to provide a model in which VcdRP employs two different molecular mechanisms to synchronize central metabolism in V. cholerae . SYNOPSIS: Traditionally considered to be non‐coding, several bacterial small regulatory RNAs (sRNAs) have been found to also encode small proteins and thus are referred to as dual‐function RNAs. Here, a forward genetic screen identifies VcdRP as the first dual‐function RNA in Vibrio cholerae, where it balances carbon uptake and metabolism. Over‐expression of VcdRP inhibits cholera toxin production. Transcription of vcdRP is controlled by cAMP‐CRP. The base‐pairing element VcdR blocks the synthesis of PTS sugar transporters. A 29 amino‐acid VcdP‐encoded protein enhances enzymatic activity of citrate synthase. Abstract : A screen for repressors of cholera toxin production identifies VcdPR as the first V. cholerae RNA that acts both as a non‐coding expression modulator and by encoding a small protein.